Systems Thinking for Sustainable Development Climate Change and the Environment - Sanneh, Edward Saja (Springer International Publishing, 2018)
This book presents a systems thinking approach in relation to the Sustainable Development Goals for sustainable national development in vulnerable countries. Systems thinking is a process for understanding the interrelationships among the key components of a system; this book illustrates sustainable development as a system. Key environmental issues are discussed showing their relationship to socioeconomic aspects of development, in the light of increased climate threats and environmental disasters.